Late Results of Anterior Cervical Discectomy and Fusion with Interbody Cages - Dağlı, Murat (Korean Society of Spine Surgery, 2013)
STUDY DESIGN: Retrospective analysis. PURPOSE: To evaluate the effectiveness of anterior cervical discectomy with fusion for degenerative cervical disc disease. OVERVIEW OF LITERATURE: Anterior spinal surgery originated in the mid-1950s and graft for fusion was also employed. Currently anterior cervical microdiscectomy and fusion with an intervertebral cage is a widely accepted procedure for treatment of cervical disc hernia. Artificial grafts and cages for fusion are preferred because of their lower morbidity, reduced operating time and acceptable fusion rate. METHODS: The study involved retrospective analysis and investigation of long-term results for 41 consecutive patients who had undergone anterior cervical discectomy and fusion with an intervertebral cage for cervical disc hernia. The angle of lordosis, segmental height and range of motion were evaluated preoperatively and postoperatively at 1 month and 2 years. The clinical outcome was assessed by the visual analog scale and Odom's criteria. RESULTS: The angle of lordosis increased by 2.62° and the range of motion angle increased by 5.14° after the operation. The segmental height did not change. The visual analog scale and Odom's criteria scores decreased significantly after the operation. CONCLUSIONS: Using a cage in anterior cervical discectomy prevents segmental collapse, so the segmental height and the angle of lordosis are preserved and newly-developed pain does not occur.